Dívida líquida e dívida bruta: Uma abordagem integrada para analisar a trajetória e o custo do endividamento brasileiro - Sérgio Wulff Gobetti; Bernardo Patta Schettini (Instituto de Pesquisa Econômica Aplicada (IPEA), 2010)
– This paper addresses a disaggregated analysis which integrates gross and net public debt or, in other words, government assets and liabilities. This approach seemed appropriate due to the recent transition in the patrimonial composition of the public sector undertaken by the means of acquisitions of foreign and domestic assets with simultaneous expansion of debt securities, mainly through repurchase agreements. We used data obtained by consolidating information disclosed in some of the Central Bank tables, adjusting for methodological changes and taking account of the institutional transition resulting from the Fiscal Responsibility Law, which has forbid the Central Bank of issuing its own bonds for monetary policy purposes. A deterministic framework was offered as a means of assessing the impact of choices concerning the debt administration and the monetary and fiscal policies on the level and cost of the public debt. The model innovates to the extent that the implicit rate of interest is endogenous. In order to deal with the composition by index of each item of the net debt, in practice the simulations were matrix-oriented. The model may be improved chiefly by taking account of stochastic uncertainty and estimating and/or calibrating the interrelations among the macroeconomic variables. An important result of the analysis is that the net debt declines in a slower fashion than what is typically predicted. The current strategy of debt administration will possibly result in an increasing implicit rate for the next years, unless interest rates decline substantially. We underscore this may imply a nonnegligible fiscal cost in the medium and long term.
Keywords: I30; I32; I38; 330